Improving the Mechanical Performance of Shell Precast Concrete Blocks for Coastal Protection Structures of Hydraulic Works - Viet Duc, N. (Engineering, Technology & Applied Science Research, 2021)
Although the use of concrete and reinforced concrete for construction has been widespread, more studies are needed on marine structures exposed directly to corrosive environments to prolong their service life. This paper proposes a new type of shell precast concrete block for coastal structures, studying a beam consisting of 15mm High-Performance Glass Fiber-Reinforced Concrete (HPGFRC) at the bottom and 45mm Traditional Concrete (TC) for the rest of the structure. Steel bar reinforcements were placed at the bottom with a concrete cover of 25mm to avoid abrupt failure. The strength classes of HPGFRC and TC were 60MPa and 30MPa respectively. A reference beam consisting of TC only was also prepared for comparison. The four-point flexural bending test results showed that the first cracking strength of the proposed beam was 20% higher, as HPGFRC performed better on tension than TC. Additionally, HPGFRC’s maximum strength was 25% greater than TC’s. Furthermore, HPGFRC possessed more durable characteristics such as waterproof grade, abrasion resistance, and shrinkage than TC, promising to protect the reinforcement from the aggressive marine environment and corrosion, prolonging the service life of the structure.